Analisis Penerapan Metode Activity Based Costing (ABC) Dalam Menentukan Tarif Sewa Kamar Kos Homestay Grace II - Farah Qalbia; Shinta Amelia (Pusat Riset dan Inovasi Nasional, 2022)
This study analyzes the application of the Activity Based Costing (ABC) method in determining boarding room rental rates at Homestay Grace II in Jakarta. The ABC method is considered more appropriate than the method that has been used by Homestay Grace II, which is to follow market rates and consider facilities. The calculation using the ABC method resulted in a room rental rate for type A of Rp. 499,657 per month and type B of Rp. 507,282 per month, lower than the rate used by Homestay Grace II. The difference in rates is due to the difference in overhead costs charged to each room. The ABC method can allocate costs more accurately based on activity consumption in each room type. The study concluded that the application of the ABC method can help boarding room rental business owners in determining more accurate and competitive rental rates. This method is considered more effective and provides more accurate information than the method that has been used by Homestay Grace II.